Tinjauan Status Nasab Seorang Anak di Luar Nikah dalam Pandangan Hukum Islam (Menurut Madzhab Syafi’i) - Umma Rosyidah, Mufti (An Nahdhoh Jurnal Kajian Islam Aswaja, 2023)
In this study, researchers will analyze the clarity of lineage status of children out of wedlock in the view of Islamic law according to the Shafi'i school of thought. The research method used is normative legal research. This type of research is library research. In this study, the lineage of children born out of wedlock in the view of Islamic law according to the Syafi'i school of thought is children born less than six months after intercourse with a legal husband. And the lineage of a child out of wedlock to his father is cut off, a child born out of wedlock only has a family relationship with his mother and his mother's family. So that it cannot be attributed to the biological father, there are no rights of inheritance, maintenance and guardianship between children born out of wedlock and their biological father.